Testing top‐down and bottom‐up effects on arid zone beetle assemblages following mammal reintroduction. (21st December 2017) - Gibb, Heloise; Verdon, Simon J.; Weir, Tom; Johansson, Therese; L'Hotellier, Felicity; Hayward, Matthew W.
Abstract: Species extinctions and declines are occurring globally and commonly have cascading effects on ecosystems. In Australia, mammal extinctions have been extensive, particularly in arid areas, where precipitation drives ecosystems. Many ecologically extinct mammals feed on soil‐dwelling insects. However, how this top‐down pressure affected their prey and how this contrasts with the bottom‐up impacts of fluctuating precipitation remains unclear. We constructed a long‐term exclusion experiment in a multi‐species mammal reintroduction zone in semi‐arid Australia to test how top‐down (reintroduced mammals) and bottom‐up (precipitation) factors affect root‐feeding chafer beetles (Coleoptera: Melolonthinae). We used emergence traps in ten replicate 20 × 20 m plots of control, exclusion and procedural control treatments to trap chafers biannually from 2009 to 2015. Annual precipitation during this period varied from 173 to 481 mm. Mammal exclusion did not affect chafers, indicating that top‐down regulation was not important. Instead, chafer abundance, species density and biomass increased with precipitation. Chafer body size and assemblage composition were best predicted by sampling year, suggesting that random drift determined species abundances. Increased resource availability therefore favoured all species similarly. We thus found no evidence that mammal predation alters chafer populations and conclude that they may be driven primarily by bottom‐up processes. Further research should determine if the cascading effects of species loss are less important for herbivores generally than for higher level trophic groups and the role of ecosystem stability in mediating these patterns.